A Trans-Species Definition of Religion - Harrod, James B. (Journal for the Study of Religion, Nature and Culture, 2011)
To advance knowledge of the evolution and prehistory of religions over the past two million years of human evolution, it would be useful to know whether other species, including great apes and extinct species of Australopithecines and Homo prior to Homo sapiens sapiens, exhibit behaviors that might be categorized as ‘religious’ or ‘spiritual’. To determine this we need a precise and robust de?nition of religious behavior suitable for cross-species comparison. I develop a non-anthropocentric and non-anthropomorphic prototype de?nition of human religious behavior and then deconstruct it into a trans-species de?nition, which can be used to predict and identify religious behavior in other species.